Perancangan E-Katalog Berbasis Web untuk Meningkatkan Promosi dan Branding Usaha UMKM Air Ikan Otista Jakarta Timur - Adnan Wahab; Fadlurohman Zaki Rifa’i; Frencis Matheos Serimole; Mesra Betty Yel (Journal Innovations Computer Science, 2026)
The increasing use of digital technology creates significant opportunities for Micro, Small, and Medium Enterprises (MSMEs) to enhance promotion and business development. Air Ikan Otista, an MSME in East Jakarta operating in the ornamental fish and aquarium supplies sector, faced limited promotional reach and unstructured product information due to conventional marketing practices. A web-based e-catalog system was designed and implemented as a digital promotion and branding medium. The study applied a qualitative approach through interviews, direct observation, and literature review, followed by structured system development using the Agile method. The system was built using Laravel as the backend framework, React JS as the frontend, and MySQL as the database. Results indicate that the e-catalog system improves the organization and consistency of product information, simplifies data management through an admin panel, and supports digital promotional activities. User Acceptance Testing (UAT) confirmed that the system is easy to operate, functionally appropriate, and acceptable for daily operations — suggesting measurable potential to strengthen promotional effectiveness and branding for MSMEs in similar sectors.